Sheets, sheeting, pilowslips, towels, napkins, counterpanes and continental quilt secondary covers suitable for use in the public sector Part 2. Specification for towels and napkins (BSI, 1988)
Towels, Table napkins, Household linen, Table linen, Baby clothing, Terry fabrics, Fabric testing, Textile testing, Cloth, Textile products, Tensile strength, Breaking load, Dimensions, Colour fastness, Sewing, Cotton, Thread (textiles), Weight (mass), Public enterprises, Pile fabrics, Designations, Textile making-up processes, Viscose